MUSLIM FAMILY RESILIENCE AMONG THE SAMBAS MALAY COMMUNITY ON TOURISM-AFFECTED LEMUKUTAN ISLAND: INTEGRATING DA'WAH AND ISLAMIC GUIDANCE AND COUNSELING PERSPECTIVES - Risma Azizah Maulani; Adiansyah; Hesty Nur Rahmi; Saripaini; Nindya Juwita Utimadini (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2026)
The development of tourism in the small archipelago has brought gradual but consistent social changes to the structure of family relationships, the division of domestic roles, and the daily interaction patterns of local communities. This study aims to analyze how Sambas Malay Muslim families in tourism-affected archipelago communities build and practice family resilience through relational, religious, and adaptive strategies in daily life. Using a qualitative approach with a case study design, the research was conducted on Lemukutan Island, Bengkayang Regency, West Kalimantan, with subjects of Sambas Malay Muslim families who have inhabited the island for generations. Data were obtained through in-depth interviews and limited observations, then analyzed using thematic analysis with a culturally and religiously sensitive approach. The findings show that the resilience of the Sambas Malay Muslim family does not manifest itself as a reactive response to acute crises, but rather as a non-confrontational social practice that is lived consistently through three dimensions: management of internal family relationships based on spiritual routines and intergenerational bonds, adjustment of interactions with tourists through structured and value-limited strategies of openness, and maintenance of family stability through the implementation of values Islam and social care across generations. The contribution of these findings lies in the designation that the resilience of Muslim families in the context of tourism is not a product of external intervention, but rather a system of layered social practices rooted in the cultural and spiritual capital of communities that have accumulated long before the wave of tourism arrives.